Evaluation of serum vitamin D and retinal nerve fibre layer thickness among type 2 diabetes mellitus patient with non proliferative diabetic retinopathy - Hooi, Tan Boon (2019)
Introduction: Retinal neurodegeneration has been postulated to be an early ocular diabetic change, preceded microangiopathy in patients with type 2 Diabetes Mellitus (DM). Other than calcium homeostasis and bone metabolism, vitamin D is found to serve as neuroprotection and prevention of angiogenesis. There is a lack of study on the relation between vitamin D and retinal neurodegeneration changes. Thus, this study evaluates on Retinal Nerve Fibre Layer (RNFL), a non-invasive technique of assessing retinal neurodegenerative changes in relation to serum vitamin D in Non Proliferative Diabetes Retinopathy (NPDR). Objective: Our objectives were to compare the mean level of serum vitamin D and RNFL thickness among type 2 DM patients with non-proliferative diabetic retinopathy (NPDR). We also aim to determine the correlation between serum vitamin D and RNFL thickness among patients with NPDR. Methods: A cross-sectional study was conducted from March 2017 to November 2018. We recruited 78 patients with type 2 DM from Ophthalmology Clinic in Hospital Universiti Sains Malaysia who fulfilled the inclusion and exclusion criteria. They were divided into 2 groups: NPDR group composed of 39 patients with mild or moderate NPDR while no DR group comprised of 39 patients without DR. International Clinical Diabetic Retinopathy Disease Severity Scales was used to grade the DR. Measurements of peripapillary RNFL were performed using Spectral Domain Optical Coherence Tomography (SD-OCT). Serum vitamin D level was analyzed using electro-chemiluminescence binding assay kit (ECLIA) produced by Roche. Definition of vitamin D level is adopted using Endocrine Society Clinical Practice Guideline. Serum vitamin D ≤ 20 ng/ml is considered as deficiency; 21-29 ng/ml as insufficiency and ≥30 ng/ml as sufficient level. Statistical analysis was done by using Statistical Package for the Social Science (SPSS Inc Version 25). The study protocol followed the tenets of the declaration of Helsinki and was approved by HREC (Human Ethics Research Committee from Hospital USM) [USM/JEPeM/ l6100410]. Results: The age of the patients ranged from 34-60 years old with the mean age of NPDR group was 55.95 years while the no DR group was 52.72 years. Most of the patients were female (62.8%) and from Malay (88.5%) ethnic. HbA1c levels were 9.13% and 7.8% respectively in NPDR group and no DR group. Both age and HbA1c were statistically significant. The serum vitamin D in both groups were found to have insufficient level with the mean serum vitamin D of 20.71[10.40]ng/ml in NPDR group and 20.93[7.65]ng/ml in no DR group. There was no statistical significance in mean serum vitamin D even after adjusted with age and HbA1c. As for RNFL thickness, the global and quadrantal thickness in NPDR group were general thinner as compares to the no DR group except the temporal quadrant of RNFL. The mean RNFL thickness in NPDR group versus the no DR group were in the following order: global (89.26[9.62]μm vs 91.28[8.00]μm), superior (110.49[21.06]μm vs 115.15[17.50]μm), nasal (65.44[10.31]μm vs 68.54[8.25]μm), inferior (108.00[23.78]μm vs 115.67[14.66]μm), temporal (67.80[10.84]μm vs 65.03[10.72]μm). After adjustment on age and HbA1c, the RNFL thickness between groups were not statistically significant. There were no correlations noted between serum vitamin D and global RNFL thickness in both groups. However, we found a weak inverse correlation between serum vitamin D and inferior quadrant thickness of RNFL in NPDR group (r= -0.37, p=0.021). Conclusion: In our study, we demonstrated that both the mean serum vitamin D and RNFL thickness were not statistically significant between the groups before and after adjusted with age and HbA1c. However, there was a weak inverse correlation between serum vitamin D level and RNFL thickness at inferior quadrant in the early stage of NPDR group. Otherwise, there was no relation noted between the serum vitamin D and others quadrantal RNFL thickness in both NPDR and no DR group. RNFL thickness measured by SD-OCT alone may not be suitable to assess retinal neurodegenerative changes in relation to serum vitamin D in NPDR. A large prospective study is needed for further evaluation on the role of vitamin D in retinal neurodegeneration in relation to RNFL thickness in early NPDR.